Maximizing Solid Organ and Face Transplant Procurement Team Coordination: The Posterior Tibial Artery Flap as an Ideal Sentinel Flap - Marissa A. Suchyta, PhD; Brian Carlsen, MD; Karim Bakri, MBBS; Hatem Amer, MD; Samir Mardini, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2023)
Face transplantation became a reality with the first case performed in 2005. Facial tissue allograft procurement is technically complex and time-intensive. Brain-dead deceased donors are frequently, if not always, multiorgan donors. Every effort should be made during face allograft recovery to minimize any risk to the recovery of lifesaving solid organs. Some programs require the procurement of a myofascial vascularized skin graft to function as a sentinel flap allowing frequent monitoring for rejection without negatively impacting the esthetics of the face graft. Up till now, the flap used has been the radial forearm flap. Procuring the radial forearm flap places the procuring team in close proximity to the head and torso, where the face recovery and the solid organ recovery teams would require unhindered access. Here, we present the posterior tibial artery flap as an alternative flap that would provide benefits to the coordination of the multiple teams working to procure organs from a deceased donor.